Rural School Success: What Can We Learn? - Zoe A. Barley; Andrea D. Beesley (Journal of Research in Rural Education, 2007)
This article reports on an exploratory study of the factors perceived by school personnel to contribute to success in highperforming, high-needs (HPHN) rural schools. It is based on earlier research in HPHN schools that identified 4 key components of success (leadership, instruction, professional community, and school environment) and explored the factors that comprise them and the relationships among them. In this study, 21 central United States rural schools were identified whose assessment scores and free and/or reduced-price lunch rates indicated that they were high-performing but also high-needs. Principals from these schools were interviewed about the factors they associate with success. Five schools subsequently received site visits that included additional interviews and focus groups of educators, school board members, parents, and community representatives. From the site visits, case studies were created to further elaborate the schools' stories. The most important perceived factors identified from telephone interviews were high expectations, focus on student learning, use of data, individualization of instruction, teacher retention and professional development, and alignment of curriculum with assessment. The case studies revealed that although schools differed in context, they all reported a supportive relationship with their community, high teacher retention, and high expectations for students. The close relationship with the community was thought to help schools enact high expectations and facilitate principal leadership. Further work is needed to identify factors distinguishing high-performing, high-needs schools from low-performing, high-needs rural schools.